2019
DOI: 10.9740/mhc.2019.07.280
|View full text |Cite
|
Sign up to set email alerts
|

A review of citalopram dose restrictions in the treatment of neuropsychiatric disorders in older adults

Abstract: Introduction Neuropsychiatric disorders affect millions of older adults. Despite this, there are relatively few older adults included in clinical trials evaluating treatments for psychiatric disorders. Citalopram has been evaluated in older adults with neuropsychiatric disorders and has largely been found beneficial, making the 2011 US Food and Drug Administration (FDA) safety advisory on citalopram extremely impactful. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In fact, in August 2011, the FDA announced a safety warning recommending to limit the maximum dose of citalopram to 20 mg/day in elderly patients aged > 60 years because of the possible occurrence of QT prolongation [104]. Therefore, it has been suggested that lower doses (< 30 mg/day) of citalopram [103] or alternatively other non-cardiotoxic antidepressants should be evaluated in clinical trials [105].…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…In fact, in August 2011, the FDA announced a safety warning recommending to limit the maximum dose of citalopram to 20 mg/day in elderly patients aged > 60 years because of the possible occurrence of QT prolongation [104]. Therefore, it has been suggested that lower doses (< 30 mg/day) of citalopram [103] or alternatively other non-cardiotoxic antidepressants should be evaluated in clinical trials [105].…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Of note, for patients older than 60 years, there exists an FDA warning of dose-dependent QTc increase with the usage of citalopram at doses greater than 20 mg. QTc data in the FDA's original drug safety warning showed an approximate 4 ms difference between 20 mg/day and 40 mg/ day [37]. But the clinical implication of this warning is unclear [38]. Studies of sertraline (50-100 mg) use in treating FTD symptoms are limited to mainly observational studies [39].…”
Section: Treatmentmentioning
confidence: 99%
“…We found that a high dose of citalopram/escitalopram was associated with a higher risk of recurrent falls compared to high dose sertraline, however, this relationship was not observed at low or medium doses. Guidance from the Food and Drug Administration (FDA) restricts the use of high dose citalopram (defined as over 20 mg daily) in adults over the age of 60 due to a potential risk of abnormal heart rhythms 23,24 . These FDA restrictions were issued in 2012 during the time our second MCBS cohort was surveyed (2012–2013).…”
Section: Discussionmentioning
confidence: 99%
“…High‐dose citalopram could be associated with abnormal heart rhythms, such as QT prolongation, which often result in dizziness, fainting spells, and an erratic heartbeat, all risk factors for falls. While citalopram has been implicated in QT interval prolongation on electrocardiogram (ECG), 25 there is limited evidence linking it to adverse cardiac outcomes 23 . However, falls and QT prolongation have shared risk factors including female sex, advancing age, and comorbidities such as stroke and diabetes 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation